1977
DOI: 10.1017/s0043174500032987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trifluralin and Metribuzin Combinations on Soybean Tolerance to Metribuzin

Abstract: In field trials, soybeans [Glycine max(L.) Merr.] treated with trifluralin [α,α,α-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine] at 0.56 and 0.84 kg/ha were protected from injury by metribuzin [4-amino-6-tert-butyl-3-(methylthio-as-triazine-5(4H)one] at 0.28 to 1.12 kg/ha. Soybean injury from metribuzin at high soil pH values was reduced by applying it in combination with trifluralin. Trifluralin also protected soybeans from injury caused by low rates of atrazine [2-chloro-4-(ethylamino)-6-(isopropylamino)-s-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…As negative effects on plant growth were also observed in noninoculated lentil grown in KN03-supplemented plant nutrient solution, this suggests that metribuzin treatment primarily affects plant growth rather than R. leguminosarum activity. Detrimental effects of photosynthesis-inhibiting herbicides on both inoculated and noninoculated legumes have been observed by others (Bollich et al 1985;Fischer and Tasistro 1982;Friesen and Wall 1986;Kao and Wang 198 1 ;Ladlie et al 1977;Mallik and Tesfai 1985). Rennie and Dubetz (1984) reported that while metribuzin applied preemergence on soybean decreased germination and plant growth, C2H2 reduction activity was higher than for control plants.…”
Section: Discussionmentioning
confidence: 77%
“…As negative effects on plant growth were also observed in noninoculated lentil grown in KN03-supplemented plant nutrient solution, this suggests that metribuzin treatment primarily affects plant growth rather than R. leguminosarum activity. Detrimental effects of photosynthesis-inhibiting herbicides on both inoculated and noninoculated legumes have been observed by others (Bollich et al 1985;Fischer and Tasistro 1982;Friesen and Wall 1986;Kao and Wang 198 1 ;Ladlie et al 1977;Mallik and Tesfai 1985). Rennie and Dubetz (1984) reported that while metribuzin applied preemergence on soybean decreased germination and plant growth, C2H2 reduction activity was higher than for control plants.…”
Section: Discussionmentioning
confidence: 77%
“…Reduced uptake of xylem-mobile triazine herbicides was observed in soybean [Glycine max (L.) Merr.] plants treated with root inhibitory dinitroaniline herbicides (Ladlie et al 1977). A similar mechanism reduced simazine injury to ornamentals by 40 to 80% when tank mixed with oryzalin or napropamide (Ryan et al 1981).…”
Section: Introductionmentioning
confidence: 92%
“…Interactions can take place between herbicides in soil. Ladlie et al (1977) reported that on a high-pH soil, trifluralin plus metribuzin caused less injury to soybean compared with a single application of metribuzin. Results from greenhouse studies indicated that trifluralin also reduced corn injury from atrazine.…”
Section: Introductionmentioning
confidence: 99%